Evaluation of attenuative potential of flaxseeds in high-calorie, high-fat, and fructose-induced metabolic syndrome indicators in Wistar rats without dietary reversal - Babi Dutta, Archana Parampalli Raghavendra, Aparna Tripathy, Deepak Nayak Manel, Shashikiran Umakanth, Shobha U. Kamath (Journal of Applied Pharmaceutical Science, 2025)
The study investigates the effects of flaxseed extract on metabolic syndrome parameters in male Wistar rats fed a high-calorie, high-fat, and fructose diet, without diet reversal, in response to the increasing incidence of western diet-induced obesity-associated metabolic syndrome and the anti-hyperlipidemic effects of flaxseeds. Fifty-six male Wistar rats were divided into seven groups (n = 8 per group); the first group (normal controls) received a standard diet. The second group (metabolic syndrome controls) received a high-calorie, high-fat diet and fructose for 16 weeks, with induction observed at 8 weeks. The third and fourth groups received a high-calorie, high-fat diet and fructose for 16 weeks, with flaxseed extract initiated after 8 weeks at doses of 0.5 and 1.0 g/kg body weight/day (post-exposure groups). The fifth and sixth groups received a high-calorie, high-fat diet supplemented with fructose and flaxseed extract at doses of 0.5 and 1.0 g/kg body weight/day for 16 weeks (co-exposure groups). Whereas the seventh group (flaxseed controls) received a regular diet and flaxseed extract (1.0 g/kg body weight/day) orally for 16 weeks. High-dose flaxseed extract reduces body weight, blood glucose, cholesterol, triglycerides (TAGs), uric acid, and total oxidant status, while increasing high-density lipoprotein levels. Liver histopathology indicates that co-exposure to high-dose flaxseed extract protects against fructose-induced hepatic steatosis. Thus, without dietary alterations, flaxseeds lower blood sugar, cholesterol, and TAG, and improve hepatic steatosis, thereby attenuating metabolic syndrome markers induced by high-calorie, high-fat, and fructose diets.
Keywords: Anti-hyperlipidemic, flaxseed extract, fructose, high-calorie high-fat, metabolic syndrome